Case-law of the Court of Justice of the European Union with regard to the European Citizen’s Initiative - Yocheva, Katerina (Yearbook of the Law Department, 2021)
Under consideration in the present article is the case-law of the Court of Justice of the European Union (General court and Court of Justice) in the period 2012–2022 with regard to the European Citizen’s Initiative (ECI). On the first hand under consideration is the relevant case-law of the General court regarding cases about ECI, and on the second hand there is consideration of the respective Court of Justice’s case-law with regard to judgments of the General court that have been appealed before that higher jurisdiction.